Fostering the Spirit of Learning Mathematics in Students of SD Negeri 13 Hutanamora, Samosir Regency - Ferdinand Sinuhaji; Ginting, Agus Susanto; Tarigan, Sumatera; Tarigan, Siti Ramadani Br; Ginting, Ananda Micola; Meliala, Yaresh De Dios S; Depari, Widiya Ananda Teresya Br; Bangun, Junois Pranta (Jurnal Pengabdian Masyarakat Bestari, 2024)
The purpose of the service is to foster the spirit of learning mathematics in students. The process carried out in this service is to prepare game tools and materials, compile instructions for implementing the game method, provide set problems, solve set problems by inviting students to get involved in solving set problems. The implementation method used in this service is the game method, namely the presentation of subject matter through games to create a fun, serious, and relaxed atmosphere so that students will learn happily. The results obtained from the service activities are the results of the pre test with the post test having an increase in value of 8.49%. Comparison of post test scores to the game model has an increase in scores of 8.70% in the Good category. The interpretation of the results of the service obtained is that by using the questions to the game can help to analyze to get decisions and results.